2020
DOI: 10.1016/j.molcel.2020.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Interferon Signaling Is Regulated by a lncRNA INCR1 Transcribed from the PD-L1 Locus

Abstract: Highlights d INCR1 is expressed from the PD-L1 locus in interferonstimulated tumor cells d INCR1 regulates tumor interferon signaling d Silencing INCR1 sensitizes tumor cells to T cell-mediated killing d INCR1 binds HNRNPH1 to promote PD-L1 and JAK2 expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 96 publications
1
43
0
Order By: Relevance
“…According to previous researches, lncRNAs were reported as crucial regulators in regulating cancer immunity [12]. A recent research from Mineo Marco et al reported that INCR1 knockdown can improve CAR T cell therapy via sensitizing tumor cells to cytotoxic T cell-mediated clearing [36]. Another research showed encouraging potentiality for new clinical management decisions on the basis of epigenetic regulation targeting LncMALAT1, which can coordinate with the immune system [37].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous researches, lncRNAs were reported as crucial regulators in regulating cancer immunity [12]. A recent research from Mineo Marco et al reported that INCR1 knockdown can improve CAR T cell therapy via sensitizing tumor cells to cytotoxic T cell-mediated clearing [36]. Another research showed encouraging potentiality for new clinical management decisions on the basis of epigenetic regulation targeting LncMALAT1, which can coordinate with the immune system [37].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous researches, lncRNAs were reported as crucial regulators in regulating cancer immunity (13). A recent research from Mineo Marco et al reported that INCR1 knockdown can improve CAR T cell therapy via sensitizing tumor cells to cytotoxic T cell-mediated clearing (40). Another research showed encouraging potentiality for new clinical management decisions on the basis of epigenetic regulation targeting LncMALAT1, which can coordinate with the immune system (41).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA INCR1 binds hnRNPH1, preventing its negative effect on the expression of the neighboring genes PD-L1 and JAK2. This results in increased IFN-γ signaling and affects T cell-mediated clearance of tumor cells [ 197 ].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%